Role-based fine-grained delegation constraint framework in collaborative environments - LIU Wei1; CAI Jia-yong1; HE Ye-ping1 (Tongxin xuebao, 2008)
A role-based delegation constraint method was introduced by separating role into two parts for fine-grained controlling. Three types of delegation constraints were analyzed, including temporal, prohibition and obligation. Using these constraints, conditional delegation and constrained usage was described. The former protected accepted delegation under certain conditions against diffuseness and abuse. The later constrained the usage of permission to avoid abuses of delegated permissions. An algorithm based on the graph theory for verifying the consistency of delegation constraints was presented, which had the time complexity of O（n2）.